Exploring biocidal effects of methyl salicylate and limonene toward Trogoderma granarium Everts (Journal of Entomological and Acarological Research, 2024)
The khapra beetle, Trogoderma granarium, poses a significant threat as a post-harvest pest in stored products and stands out as a crucial quarantine concern globally. Unlike many other stored product pests, this species proved challenging to manage using conventional insecticides and alternative non-chemical methods. The exploration of plant-based natural products, particularly essential oils, as alternatives arises in response to challenges associated with the prolonged use of synthetic insecticides. While essential oils show promising activity, their use encounters challenges associated with standardization. This study investigates the feasibility of employing some single chemical compounds widespread in several essential oils with insecticidal activity as candidate insecticides, specifically limonene and methyl salicylate in contact/fumigation bioassays toward T. granarium adults. The results showed that methyl salicylate caused a lethal time of 50% (LT50) at the dose of 1 mg after 7.40 hours of exposure. The LT50 calculated for limonene was 86.83 hours while positive control using deltamethrin, used at the recommended dose of the manufacturer, was 5.20 hours after exposure. These data suggest that methyl salicylate can be exploited as a candidate for further tests in field conditions toward T. granarium also in consideration of its relative low toxicity for humans.
Keywords: Khapra beetle; LT50; contact/fumigation bioassays; essential oils